Design of a 200 W Flying Capacitor Multilevel Flyback Converter - Graziani, Santino; Cook, Thomas; Grainger, Brandon (Electronics (Basel), 2024)
This directive proposes an efficiency optimization process in which the flying capacitor multilevel flyback converter (FCMFC) will be designed for the highest efficiency based on component selection, the number of flying capacitor stages, with isolation. The application of interest is a front-end voltage-boosting converter that is part of a solar microinverter. The converter will need high gain and high efficiency over a large range due to the variable input voltage supplied by the output of a solar panel. The electrical specifications are 40 V to 400 V conversion for a 200 W load; however, the input voltage and load power are subject to variability.